Comparison of molecular epidemiology of bloodstream methicillin-resistant Staphylococcus aureus isolates between a new and an old hospital in central Taiwan. (February 2019) - Lee, Chun-Yi; Fang, Yu-Ping; Chang, Yu-Fen; Wu, Tsung-Hua; Yang, Yu-Ying; Huang, Yhu-Chering
Highlights: The methicillin resistance rate of Staphylococcus aureus isolates was comparable in the new and old hospitals. The molecular epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) differed between the new and old hospitals. The molecular epidemiology of MRSA in the hospitals changed over time. Abstract: Objective: To compare the molecular epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) isolates between an old, urban hospital and a new, rural hospital over the same time period. Methods: The molecular characteristics of 398 MRSA bloodstream isolates collected between 2007 and 2013 from two hospitals in Taiwan were analyzed retrospectively; 202 isolates were from the old hospital and 196 from the new hospital (opened in 2007). Results: The rate of resistance to multiple antibiotics was significantly higher in the old hospital (93%) than in the new hospital (81%) ( p <  0.001). Genetic community-associated MRSA carrying staphylococcal cassette chromosome (SCC) type IV or V accounted for 58% of all MRSA isolates in the new hospital, significantly higher than the rate in the old hospital ( p  = 0.018). The rate of spa t037-SCC mec III MRSA was significantly lower in the new hospital than in the old hospital ( p  = 0.02). A significant decreasing trend in spa t002-SCC mec II MRSA isolates was observed in the old hospital ( p  = 0.006), while the proportion of spa t037-SCC mec III MRSA decreased significantly in the new hospital (41.7% to 26.1%, p  = 0.022). Conclusions: The rate of multiple antibiotic resistance and the molecular characteristics of MRSA differed significantly between the old and new hospitals and changed over time.